2022
DOI: 10.1007/s10668-022-02356-w
|View full text |Cite
|
Sign up to set email alerts
|

Driving factors of e-waste recycling rate in 30 European countries: new evidence using a panel quantile regression of the EKC hypothesis coupled with the STIRPAT model

Abstract: Recycling of e-waste (waste electrical and electronic equipment) represents an important abatement of pressure on the environment, but recycling rates are still low. This study builds on common environmental economics approaches to identify the main driving forces of the e-waste recycling rate. The environmental Kuznets curve hypothesis was applied in the context of the STIRPAT (stochastic impacts by regression on population, affluence and technology) model to analyze data from 30 European countries over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…Therefore, we employed panel quantile regression with non-additive fixed effects introduced by Powell [ 51 ] to overcome this problem. Similar to the studies conducted by Xu et al [ 52 ] and Boubellouta and Kusch-Brandt [ 8 ], we estimated and reported the findings for five quantiles, namely 10th, 25th, 50th, 75th, and 90th quantiles of the conditional distribution of e-waste recycling rate. In this case, the lower quantiles were represented by the countries with lower e-waste recycling rates, while the upper quantiles were represented by the countries with higher e-waste recycling rates.…”
Section: Estimation Techniquesupporting
confidence: 76%
See 4 more Smart Citations
“…Therefore, we employed panel quantile regression with non-additive fixed effects introduced by Powell [ 51 ] to overcome this problem. Similar to the studies conducted by Xu et al [ 52 ] and Boubellouta and Kusch-Brandt [ 8 ], we estimated and reported the findings for five quantiles, namely 10th, 25th, 50th, 75th, and 90th quantiles of the conditional distribution of e-waste recycling rate. In this case, the lower quantiles were represented by the countries with lower e-waste recycling rates, while the upper quantiles were represented by the countries with higher e-waste recycling rates.…”
Section: Estimation Techniquesupporting
confidence: 76%
“…This study contributes a pioneering analysis in the literature by being the first to explore the influence of government ideology on e-waste recycling rates. Previous research (Boubellouta and Kusch-Brand [ 8 ], Yilmaz and Koyuncu [ 9 ], Constantinescu et al [ 10 ]) has overlooked government ideology as a factor impacting e-waste recycling, and this study addresses this gap by introducing a new determinant affecting e-waste recycling rates. As far as our knowledge extends, no empirical research has investigated the relationship between government ideology and e-waste recycling rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations